Ultralow dielectric loss aluminate microwave dielectric material and preparation method thereof

By preparing a new aluminate microwave dielectric material, the problem of high dielectric loss in high-frequency communications is solved, and the effects of ultra-low dielectric loss and low dielectric constant are achieved, which improves the stability and efficiency of microwave signal transmission.

CN119528562AActive Publication Date: 2025-02-28NANJING INST OF TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411495539.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2025-02-28
Estimated Expiration
2044-10-25

AI Technical Summary

Technical Problem

Existing microwave dielectric ceramic materials have high dielectric losses in high-frequency communication, which affects signal transmission efficiency and system performance.

Method used

A new aluminate microwave dielectric material is used, with the chemical expression of YAZn3-xBxAlO7, where A=Sr, Ba, B=Co, Ni, 0≤x≤0.08, and the main crystal phase is a single "114" configuration compound, which is prepared by conventional solid phase sintering method.

Benefits of technology

This material has ultra-low dielectric loss (tan𝛿<10-5) and low dielectric constant. It is suitable for manufacturing resonators, filters and other devices, significantly improving the stability and efficiency of microwave signal transmission.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119528562A_ABST
    Figure CN119528562A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminate microwave dielectric material with ultralow dielectric loss and a preparation method thereof, the chemical expression of the aluminate microwave dielectric material is YAZn3-xBxAlO7, A = Sr and Ba, B = Co and Ni, and x is more than or equal to 0 and less than or equal to 0.08. The preparation process sequentially comprises the following steps: synthesizing ceramic powder by a solid-phase reaction method, ball-milling, pressing and forming, and sintering to obtain the ceramic. The main crystal phase of the aluminate microwave dielectric material with ultralow dielectric loss is a single-phase '114' configuration compound, and the aluminate microwave dielectric material has the advantages of low raw material cost, low dielectric constant (10-15), high Qf value (102000-255000GHz), simple preparation process, good reproducibility and the like, can solve the time delay problem of microwave signals in high-frequency communication, improves the transmission stability of the microwave signals, and has wide application prospects. The method is very suitable for manufacturing resonators, filters, dielectric substrates, dielectric antennas and other devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of microwave dielectric ceramics, and in particular relates to an ultra-low dielectric loss aluminate microwave dielectric material and a preparation method thereof. Background Art

[0002] Microwave dielectric ceramics are widely used in modern communication technologies, including frequency-stabilized oscillators, filters, dielectric resonators, dielectric substrates, antennas, and chip capacitors, etc. They can meet the requirements of modern microwave communications, mobile communications, satellite communications, radio and television, radar, electronic countermeasures, guidance, and other technologies for microwave circuit integration, miniaturization, high reliability, and low cost. In particular, with the development of 5G and 6G technologies, the application of microwave dielectric ceramics in the radio frequency units of communication base stations has become more important and has become an indispensable key component in communication systems.

[0003] With the continuous advancement of communication technology, the performance requirements for microwave devices are getting higher and higher, especially the demand for low-loss, high-Q value materials is increasing. Super dielectric loss microwave dielectric ceramics can significantly reduce the insertion loss of devices and improve signal transmission efficiency, thereby improving the overall performance of communication systems. Super dielectric loss microwave dielectric ceramics also have broad application prospects in high-end application fields such as satellite communications, Beidou navigation, and electronic countermeasures, and can significantly improve the technical level and competitiveness of these fields.

[0004] Aluminate microwave dielectric ceramics are an important microwave dielectric material. Due to their excellent dielectric properties and good temperature stability, they have received extensive attention and research in the field of microwave communications in recent years. Aluminate microwave dielectric ceramics mainly include CaAl 2 O 4 , CaAl 4 O 7 These materials have the advantages of low dielectric constant, low dielectric loss and near-zero resonant frequency temperature coefficient, making them of great application value in high-frequency electronic equipment. The present invention discloses an ultra-low dielectric loss aluminate microwave dielectric material and a preparation method thereof. The compound has ultra-low dielectric loss (tan𝛿<10 -5 ), and has a low dielectric constant, which makes it very suitable for manufacturing devices such as resonators, filters, dielectric substrates and dielectric antennas. It is widely used in satellite communications, Beidou navigation, electronic countermeasures, 5G, the Internet of Things and other fields. Summary of the invention

[0005] The purpose of the present invention is to provide an ultra-low dielectric loss aluminate microwave dielectric material and a preparation method thereof. The main crystal phase of the material is a single "114" configuration compound, which has the advantages of low cost, low dielectric constant, ultra-low dielectric loss, strong resistance to reduction, and stable preparation process.

[0006] The present invention discloses an ultra-low dielectric loss aluminate microwave dielectric material, characterized in that the chemical expression of the aluminate microwave dielectric material is Y A Zn 3-x B x AlO 7 ,in A =Sr, Ba, B =Co, Ni, 0≤ x ≤0.08.

[0007] The main crystal phase of the aluminate microwave dielectric material is a single "114" configuration compound.

[0008] A method for preparing an ultra-low dielectric loss aluminate microwave dielectric material, characterized by comprising the following steps: Step 1: Porcelain powder synthesis: Y 2 O 3 、SrCO 3 、BaCO 3 , ZnO, CoO, NiO and Al 2 O 3 High purity powder is used as raw material, according to the chemical formula Y A Zn 3-x B x AlO 7 ( A =Sr, Ba, B =Co, Ni, 0≤ x ≤0.08) to weigh and mix the ingredients to form a mixed powder; the mixed powder is placed in a planetary ball mill for wet grinding, the grinding balls are made of zirconium dioxide, the mass ratio of the mixed material, grinding balls and ball milling medium is 1:5:1.2, the ball milling time is 6 hours, and the ball mill speed is 300 rpm; after drying, the mixed powder is transferred to an alumina crucible, placed in a box-type resistance furnace and heated to 1150~1200℃, kept warm for 4~6 hours and then cooled to room temperature.

[0009] Step 2, ball milling: transfer the synthesized aluminate porcelain powder to a nylon ball mill, add ball milling media and grinding balls, and place it in a planetary ball mill for wet grinding. The grinding balls are made of zirconium dioxide, and the mass ratio of the mixture, grinding balls and ball milling media is 1:5:1.2. The ball milling time is 8-12 hours, and the ball mill speed is 250-350 rpm; Step 3: Pressing and forming: After drying the ball mill slurry, add 5-8 wt% of the weight of the binder, mix, sieve and granulate; press into a green body on a unidirectional press at a pressure of 100-150 MPa; Step 4, sintering into porcelain: Place the pressed green sheet in a box-type resistance furnace and heat it slowly to 500°C, keep it warm for 2 hours, then heat it to 650°C, keep it warm for 2 hours, then heat it to 1350~1450°C, keep it warm for 4~8 hours, and finally cool it with the furnace to obtain an ultra-low dielectric loss aluminate microwave dielectric material.

[0010] The Y 2 O 3 、SrCO 3 、BaCO 3 , ZnO, CoO, NiO and Al 2 O 3 The particle size of the powder is 1~5μm and the purity is ≥99.5%.

[0011] The ball milling medium is anhydrous ethanol or deionized water.

[0012] The adhesive is a polyvinyl alcohol aqueous solution with a concentration of 5wt%.

[0013] The present invention has the beneficial effects: (1) The present invention prepares a single-phase "114" configuration compound by conventional solid-phase sintering method. The compound has a special tetrahedral coordination layer. The crystal structure of the compound can be appropriately distorted by substitution with trace amounts of Co and Ni, thereby significantly reducing the dielectric loss of the compound.

[0014] 2) The dielectric constant of the ultra-low dielectric loss aluminate microwave dielectric material prepared by the present invention is 10~15, Q f The value is 102000~255000GHz, which can solve the delay problem of microwave signals in high-frequency communications and improve the stability of microwave signal transmission. It is very suitable for use as microwave substrates, dielectric antennas and other systems.

[0015] (3) The ultra-low dielectric loss aluminate microwave dielectric material provided by the present invention has a simple preparation process, low raw material cost, no pollution to the environment, and good production process stability, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is the XRD spectrum of the ultra-low dielectric loss aluminate microwave dielectric material prepared in Example 3 of the present invention.

[0017] Figure 2 YSrZnAlO prepared in Example 3 of the present invention 7 XRD structure refinement diagram.

[0018] Figure 3 YSrZnAlO prepared in Example 3 of the present invention 7 Microstructure diagram of . DETAILED DESCRIPTION

[0019] The present invention is further described below. The following examples are only used to more clearly illustrate the technical solution of the present invention, and are not intended to limit the protection scope of the present invention.

[0020] Table 1 shows the mixed powders of 5 ingredients. Ultra-low dielectric loss aluminate microwave dielectric materials were prepared by using different process parameters, and their microwave dielectric properties were measured respectively.

[0021] Y 2 O 3 、SrCO 3 、BaCO 3 , ZnO, CoO, NiO and Al 2 O 3 High purity powder is used as raw material, according to the chemical formula Y A Zn 3-x B x AlO 7 ( A =Sr, Ba, B =Co, Ni, 0≤ x ≤0.08) Table 1 Mixture of five ingredients (mol%) Element <![CDATA[Y 2 THE 3 ]]> <![CDATA[SrCO 3 ]]> <![CDATA[BaCO 3 ]]> ZnO CoO NiO <![CDATA[Al 2 THE 3 ]]> <![CDATA[1 # ]]> 1 2 6 1 <![CDATA[2 # ]]> 1 2 6 1 <![CDATA[3 # ]]> 1 2 5.84 0.16 1 <![CDATA[4 # ]]> 1 2 5.84 0.16 1 <![CDATA[5 # ]]> 1 2 5.90 0.10 1 Embodiment 1

[0022] Step 1: Porcelain powder synthesis: Y 2 O 3 、SrCO 3 、BaCO 3 , ZnO, CoO, NiO and Al 2 O 3 High-purity powder was used as raw material, and the ingredients were weighed and prepared according to Table 1 to form a mixed powder; the mixed powder was placed in a planetary ball mill for wet grinding, the grinding ball material was zirconium dioxide, the mass ratio of the mixture, grinding balls and ball milling medium was 1:5:1.2, the ball milling time was 6 hours, and the ball mill speed was 300rpm; after drying, the mixed powder was transferred to an alumina crucible, placed in a box-type resistance furnace, heated to 1150°C, kept warm for 6 hours, and then cooled to room temperature.

[0023] Step 2, ball milling: the synthesized aluminate porcelain powder is transferred to a nylon ball mill, anhydrous ethanol and grinding balls are added, and the mixture is wet-milled in a planetary ball mill. The grinding balls are made of zirconium dioxide, and the mass ratio of the mixture, the grinding balls and the anhydrous ethanol is 1:5:1.2. The ball milling time is 8 hours, and the ball mill speed is 350 rpm. Step 3, pressing and molding: after drying the ball mill slurry, add 5wt% of the weight of the slurry and a 5wt% polyvinyl alcohol aqueous solution, mix, sieve and granulate; press into a green body at a pressure of 100MPa on a unidirectional press; Step 4, sintering into porcelain: Place the pressed green sheet in a box-type resistance furnace and heat it slowly to 500°C, keep it warm for 2 hours, then heat it to 650°C, keep it warm for 2 hours, then heat it to 1350°C, keep it warm for 8 hours, and finally cool it with the furnace to obtain an ultra-low dielectric loss aluminate microwave dielectric material.

[0024] The performance of the material obtained in this example was tested, and the test results are shown in Table 2.

[0025] Table 2 Dielectric properties of different materials prepared using Example 1 Element <![CDATA[1 # ]]> <![CDATA[2 # ]]> <![CDATA[3 # ]]> <![CDATA[4 # ]]> <![CDATA[5 # ]]> Dielectric constant 12.5 10 12.1 10.7 12.3 Q value (GHz) 117500 102000 158500 165100 187800 <![CDATA[ τ f (ppm / ℃)]]> -45.8 -40.2 -48.4 -42.7 -41.5 Embodiment 2

[0026] Step 1: Porcelain powder synthesis: Y 2 O 3 、SrCO 3 、BaCO 3 , ZnO, CoO, NiO and Al 2 O 3 High-purity powder was used as raw material, and the ingredients were weighed and prepared according to Table 1 to form a mixed powder; the mixed powder was placed in a planetary ball mill for wet grinding, the grinding ball material was zirconium dioxide, the mass ratio of the mixture, grinding balls and ball milling medium was 1:5:1.2, the ball milling time was 6 hours, and the ball mill speed was 300rpm; after drying, the mixed powder was transferred to an alumina crucible, placed in a box-type resistance furnace and heated to 1200℃, kept warm for 4 hours and then cooled to room temperature.

[0027] Step 2, ball milling: transfer the synthesized aluminate porcelain powder to a nylon ball mill, add deionized water and grinding balls, and place it in a planetary ball mill for wet grinding. The grinding balls are made of zirconium dioxide, and the mass ratio of the mixture, grinding balls and deionized water is 1:5:1.2. The ball milling time is 12 hours, and the ball mill speed is 250 rpm; Step 3, pressing and molding: After drying the ball mill slurry, add 8wt% of its weight of a 5wt% polyvinyl alcohol aqueous solution, mix, sieve, and granulate; press into a green body on a uniaxial press at a pressure of 150MPa; Step 4, sintering into porcelain: Place the pressed green sheet in a box-type resistance furnace and heat it slowly to 500°C, keep it warm for 2 hours, then heat it to 650°C, keep it warm for 2 hours, then heat it to 1450°C, keep it warm for 4 hours, and finally cool it with the furnace to obtain an ultra-low dielectric loss aluminate microwave dielectric material.

[0028] The performance of the material obtained in this example was tested, and the test results are shown in Table 3.

[0029] Table 3 Dielectric properties of different materials prepared using Example 2 Element <![CDATA[1 # ]]> <![CDATA[2 # ]]> <![CDATA[3 # ]]> <![CDATA[4 # ]]> <![CDATA[5 # ]]> Dielectric constant 15 12.3 14.3 12.9 14.8 Q value (GHz) 193200 165200 215500 185500 235600 <![CDATA[ τ f (ppm / ℃)]]> -41.3 -42.8 -45.5 -40.9 -44.3 Embodiment 3

[0030] Step 1: Porcelain powder synthesis: Y 2 O 3 、SrCO 3 、BaCO 3 , ZnO, CoO, NiO and Al 2 O 3 High-purity powder was used as raw material, and the ingredients were weighed and prepared according to Table 1 to form a mixed powder; the mixed powder was placed in a planetary ball mill for wet grinding, the grinding ball material was zirconium dioxide, the mass ratio of the mixture, grinding balls and ball milling medium was 1:5:1.2, the ball milling time was 6 hours, and the ball mill speed was 300rpm; after drying, the mixed powder was transferred to an alumina crucible, placed in a box-type resistance furnace and heated to 1175°C, kept warm for 5 hours and then cooled to room temperature.

[0031] Step 2, ball milling: the synthesized aluminate porcelain powder is transferred to a nylon ball mill, anhydrous ethanol and grinding balls are added, and the mixture is wet-milled in a planetary ball mill. The grinding balls are made of zirconium dioxide, and the mass ratio of the mixture, the grinding balls and the anhydrous ethanol is 1:5:1.2. The ball milling time is 10 hours, and the ball mill speed is 300 rpm. Step 3, pressing and molding: After drying the ball mill slurry, add 6wt% of its weight and 5wt% polyvinyl alcohol aqueous solution, mix, sieve and granulate; press into a green body on a uniaxial press at a pressure of 125MPa; Step 4, sintering into porcelain: Place the pressed green sheet in a box-type resistance furnace and heat it slowly to 500°C, keep it warm for 2 hours, then heat it to 650°C, keep it warm for 2 hours, then heat it to 1400°C, keep it warm for 6 hours, and finally cool it with the furnace to obtain an ultra-low dielectric loss aluminate microwave dielectric material.

[0032] The performance of the material obtained in this example was tested, and the test results are shown in Table 4.

[0033] Table 4 Dielectric properties of different materials prepared using Example 3 Element <![CDATA[1 # ]]> <![CDATA[2 # ]]> <![CDATA[3 # ]]> <![CDATA[4 # ]]> <![CDATA[5 # ]]> Dielectric constant 14.2 11.3 13.5 11.6 13.6 Q value (GHz) 216300 177300 223100 194500 255000 <![CDATA[ τ f (ppm / ℃)]]> -45.2 -45.1 -45.5 -40.9 -45.8 The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. An ultra-low dielectric loss aluminate microwave dielectric material, characterized in that: The chemical expression of the aluminate microwave dielectric material is Y A Zn 3-x B x AlO7, among which A =Sr, Ba, B =Co, Ni, 0≤ x ≤0.

08.

2. The ultra-low dielectric loss aluminate microwave dielectric material according to claim 1, characterized in that: The main crystal phase of the aluminate microwave dielectric material is a single "114" configuration compound.

3. A method for preparing an ultra-low dielectric loss aluminate microwave dielectric material, characterized in that: The steps include: Step 1: Porcelain powder synthesis: using high-purity powders of Y2O3, SrCO3, BaCO3, ZnO, CoO, NiO and Al2O3 as raw materials, single-phase aluminate porcelain powder is prepared by solid phase sintering method; Step 2, ball milling: transfer the synthesized aluminate porcelain powder to a nylon ball mill, add ball milling media and grinding balls, and place it in a planetary ball mill for wet grinding. The grinding balls are made of zirconium dioxide, and the mass ratio of the mixture, grinding balls and ball milling media is 1:5:1.

2. The ball milling time is 8-12 hours, and the ball mill speed is 250-350 rpm; Step 3: Pressing and forming: After drying the ball mill slurry, add 5-8 wt% of the weight of the binder, mix, sieve and granulate; press into a green body on a unidirectional press at a pressure of 100-150 MPa; Step 4, sintering into porcelain: Place the pressed green sheet in a box-type resistance furnace and heat it up slowly to 500°C, keep it warm for 2 hours, then heat it up to 650°C, keep it warm for 2 hours, then heat it up to the sintering temperature and keep it warm, and finally cool it with the furnace to obtain an ultra-low dielectric loss aluminate microwave dielectric material.

4. The method for preparing an ultra-low dielectric loss aluminate microwave dielectric material according to claim 3, characterized in that: The particle size of the Y2O3, SrCO3, BaCO3, ZnO, CoO, NiO and Al2O3 powders described in step 1 is 1~5μm, and the purity is ≥99.5%.

5. The method for preparing an ultra-low dielectric loss aluminate microwave dielectric material according to claim 3, characterized in that: The specific method for preparing the single-phase aluminate porcelain powder by the solid phase sintering method in step 1 is: Y2O3, SrCO3, BaCO3, ZnO, CoO, NiO and Al2O3 raw material powders are sintered according to the chemical formula Y A Zn 3-x B x AlO7( A =Sr, Ba, B =Co, Ni, 0≤ x ≤0.08) to weigh and mix the ingredients to form a mixed powder; the mixed powder is placed in a planetary ball mill for wet grinding, the grinding balls are made of zirconium dioxide, the mass ratio of the mixed material, grinding balls and ball milling medium is 1:5:1.2, the ball milling time is 6 hours, and the ball mill speed is 300rpm; after drying, the mixed powder is transferred to an alumina crucible, placed in a box-type resistance furnace and heated to 1150~1200℃, kept warm for 4~6h and then cooled to room temperature.

6. The method for preparing an ultra-low dielectric loss aluminate microwave dielectric material according to claim 3, characterized in that: The ball milling medium in step 2 is anhydrous ethanol or deionized water.

7. The method for preparing an ultra-low dielectric loss aluminate microwave dielectric material according to claim 3, characterized in that: The adhesive in step three is a polyvinyl alcohol aqueous solution with a concentration of 5wt%.

8. The method for preparing an ultra-low dielectric loss aluminate microwave dielectric material according to claim 3, characterized in that: The sintering temperature in step 4 is in the range of 1350-1450° C., and the temperature is kept at 4-8 hours.

Citation Information

Patent Citations

  • Microwave ceramic dielectric material and preparation method thereof

    CN103626488A

  • Low-dielectric-constant high-frequency glass ceramic LTCC material and preparation method thereof

    CN106673446A

  • Low dielectric and low loss boride LTCC material and preparation method thereof

    CN114180939A